Off-season biogenic volatile organic compound emissions from heath mesocosms: responses to vegetation cutting - Rinnan, Riikka; Gierth, Diana; Bilde, Merete; Rosenørn, Thomas; Michelsen, Anders (Frontiers in Microbiology, 2013)
Biogenic volatile organic compounds (BVOCs) affect both atmospheric processes and ecological interactions. Our primary aim was to differentiate between BVOC emissions from above- and belowground plant parts and heath soil outside the growing season. The second aim was to assess emissions from herbivory, mimicked by cutting the plants. Mesocosms from a temperate Deschampsia flexuosa-dominated heath ecosystem and a subarctic mixed heath ecosystem were either left intact, the aboveground vegetation was cut, or all plant parts (including roots) were removed. For 3–5 weeks, BVOC emissions were measured in growth chambers by an enclosure method using gas chromatography-mass spectrometry. CO2 exchange, soil microbial biomass, and soil carbon and nitrogen concentrations were also analyzed. Vegetation cutting increased BVOC emissions by more than 20-fold, and the induced compounds were mainly eight-carbon compounds and sesquiterpenes. In the Deschampsia heath, the overall low BVOC emissions originated mainly from soil. In the mixed heath, root, and soil emissions were negligible. Net BVOC emissions from roots and soil of these well-drained heaths do not significantly contribute to ecosystem emissions, at least outside the growing season. If insect outbreaks become more frequent with climate change, ecosystem BVOC emissions will periodically increase due to herbivory.